2023
DOI: 10.3390/nu15092116
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Creatine Supplementation Combined with Resistance Training on Regional Measures of Muscle Hypertrophy: A Systematic Review with Meta-Analysis

Abstract: The purpose of this paper was to carry out a systematic review with a meta-analysis of randomized controlled trials that examined the combined effects of resistance training (RT) and creatine supplementation on regional changes in muscle mass, with direct imaging measures of hypertrophy. Moreover, we performed regression analyses to determine the potential influence of covariates. We included trials that had a duration of at least 6 weeks and examined the combined effects of creatine supplementation and RT on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As an extension of the above, it is well understood that the ergogenic effects of creatine supplementation on muscular performance are most potent when combined with resistance training and consumed chronically [64,65]. For example, the results of a recent metaanalysis indicated that creatine supplementation resulted in great increases in lean tissue mass, leg press strength, and chest press strength during resistance training compared to resistance training alone in older adults [66].…”
Section: Discussionmentioning
confidence: 99%
“…As an extension of the above, it is well understood that the ergogenic effects of creatine supplementation on muscular performance are most potent when combined with resistance training and consumed chronically [64,65]. For example, the results of a recent metaanalysis indicated that creatine supplementation resulted in great increases in lean tissue mass, leg press strength, and chest press strength during resistance training compared to resistance training alone in older adults [66].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several meta-analyses have been performed collectively showing that the combination of creatine supplementation and resistance exercise increases measures of whole-body lean tissue mass by ~1.37 kg (as measured by dual-energy X-ray absorptiometry, air-displacement plethysmography, hydrodensitometry, and bioelectrical impedance analysis) compared to placebo and resistance exercise [28][29][30][31][32]. Furthermore, Burke et al [33] performed a systematic review and meta-analysis involving 10 studies and found significant improvements in direct measures of limb muscle hypertrophy (0.10-0.16 cm; as measured using ultrasound and peripheral quantitative computed tomography {pQCT}) in the upper-and lower-body from creatine supplementation and resistance exercise compared to resistance exercise and placebo. Interestingly, the lone study that used pQCT showed that creatine supplementation (52 weeks) increased lower-limb muscle density (∆ + 0.83 ± 1.15 mg•cm −3 ; p = 0.016) compared to placebo (∆ −0.16 ± 1.56 mg•cm −3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limited number of included studies that used BIA as body composition measurement tools (8 of 143 studies) or provided body water data, more studies are needed to confirm body water retention changes following creatine supplementation. A recent systematic review and meta-analysis involving 10 studies showed that the combination of creatine supplementation and resistance training increased regional measures of muscle accretion (0.10 to 0.16 cm; as measured using ultrasound and peripheral quantitative computed tomography) compared to placebo [ 23 ]. Mechanistically, greater fat-free mass from creatine is likely related to its ability to increase high-energy phosphate, glycogen, calcium, and protein kinetics, stimulation of satellite cells and growth factors, or by decreasing inflammation and oxidative stress over time [ 2 , 179 ].…”
Section: Loading Protocol Of Creatine Supplementation and Training In...mentioning
confidence: 99%
“…To date, two meta-analyses have been performed showing that the combination of creatine supplementation and resistance training results in very small reductions in body fat percentage compared to resistance training alone [ 21 , 22 ]. Lastly, there is evidence that sex [ 12 ] and age [ 23 ] differences may exist regarding muscle changes over time, however, the effects on other indices of body composition are unknown. Collectively, this study aimed to systematically review randomized controlled trials (RCTs) evaluating the effects of creatine supplementation on body composition and to determine if the dosing protocol, exercise type, or alternative forms of creatine, as well as sex and age, influence the results.…”
Section: Introductionmentioning
confidence: 99%